Development of Zakat in Indonesia : Which are the Priority Aspects? - Ali, Khalifah Muhamad; Rusydiana, Aam Slamet; Khalifah, Mohamad Handi (SMART Insight, 2023)
This research aims to identify prioritized strategies within the scope of zakat development in Indonesia. The research method employed is the Analytic Network Process (ANP), utilizing primary data sourced from in-depth interviews with the respondents who are experts, practitioners, and regulators possessing a comprehensive understanding of the pertinent subject matter. The research findings reveal that the foremost priorities across the respective facets investigated in the context of zakat development in Indonesia are the amil competence aspect, followed by the regulatory aspect, sharia compliance aspect, collection aspect, utilization aspect, and institutional framework aspect. Subsequently, within each aspect, the sub-criteria priorities are determined to be the amil competence standard, regulatory refinement, fiqh zakat standard, IT-based collection, ashaf-based map for mustahik, and performance management. The implications of this research proffer recommendations for pertinent stakeholders to further cultivate zakat in Indonesia through the identified priority facets. Furthermore, for future research endeavors, scholars are encouraged to delve deeper into the exploration of prioritized aspects and employ alternative methods or analytical tools that remain pertinent.